Short-Term Outcome and Hemodynamic Performance of Next-Generation Self-Expanding Versus Balloon-Expandable Transcatheter Aortic Valves in Patients With Small Aortic Annulus: A Multicenter Propensity-Matched Comparison. (October 2017) - Mauri, Victor; Kim, Won K.; Abumayyaleh, Mohammad; Walther, Thomas; Moellmann, Helge; Schaefer, Ulrich; Conradi, Lenard; Hengstenberg, Christian; Hilker, Michael; Wahlers, Thorsten; Baldus, Stephan; Rudolph, Volker; et al.
Abstract : Background—: Surgical aortic valve replacement in patients with small annular dimensions is challenging because they are at increased risk for prosthesis–patient mismatch and impaired outcomes. Transcatheter aortic valve replacement might be a good alternative; however, comparative data on different transcatheter heart valves are missing. Methods and Results—: This multicenter, propensity score–matched study compared hemodynamics and early clinical outcomes in 246 patients with an aortic annulus area <400 mm 2 undergoing transcatheter aortic valve replacement with either a self-expanding transcatheter heart valve (Symetis ACURATE neo, n=129) or a balloon-expandable transcatheter heart valve (Edwards SAPIEN 3, n=117). The 1:1 propensity score matching resulted in 92 matched pairs. For ACURATE neo versus SAPIEN 3-treated patients, 30-day mortality (0.0% versus 1.0%), 1-year mortality (8.3% versus 13.3%), incidence of stroke (3.3% versus 2.2%), life-threatening bleeding (1.1% versus 1.1%), and major vascular complications (2.2% versus 6.5%), as well as pacemaker implantation rate (12.0% versus 15.2%), were similar. Paravalvular regurgitation ≥moderate was rare in both groups (4.5% versus 3.6%). The ACURATE neo presented lower mean transvalvular gradients (9.3 versus 14.5 mm Hg; P <0.001), larger indexed effective orifice areas (0.96 versus 0.80 cm 2 /m 2 ; P =0.003), and lower rates of severe prosthesis–patient mismatch (3% versus 22%; P =0.004). Hemodynamics were sustained at 1-year follow-up. Conclusions—: Albeit a similar safety profile with low clinical event rates, transcatheter aortic valve replacement with the ACURATE neo valve resulted in lower transvalvular gradients and consequently less prosthesis–patient mismatch compared with the SAPIEN 3 in patients with small annulus. These results emphasize the need of careful prosthesis selection in each individual patient. Abstract : Supplemental Digital Content is available in the text.